Stochastic Approach to Estimating Stresses of Polymer Films from the Surface Microprofile - Pashayev, A.M.; Janahmadov, A.Kh. (Herald of Azerbaijan Engineering Academy, 2021)
The existing methods for determining the internal (residual, shrinkage) stresses arising from the curing of thin films of paint and varnish coatings (PVC), based on the cantilever bending of the substrate and the difference in the thicknesses of the wet and dry coatings, are analyzed. The dependence of their accuracy on the film / substrate thickness ratio and the uniformity of the applied film is noted. The application of atomic force microscopy methods based on measuring the geometry of the regular microrelief (RMR) of the film surface, which serves as a characteristic manifestation of its shrinkage deformations, is considered. It is noted that when applying the Euler problem on the stability of a compressed rod, the method demonstrates the calculated stress values unattainable for most polymers. The calculation of internal stresses and strains was carried out on the basis of a stochastic approach, taking into account the "checkerboard" distribution of deformation defects on the outer surface of the film. On the example of RMR film of polyester urethane varnish, the level of internal stresses was assessed using the proposed and existing methods. The values of internal stresses obtained by the three methods relatively coincide with each other, the difference between them does not exceed ~20%.